Avaliação da sustentabilidade financeira de entidades de assistência social - Silva, José Roberto da (2010)
This study aims to evaluate the financial sustainability of Third Sector entities, especially entities of Social Assistance. The research is guided by quantitative nature. The data used originate from the database of Serasa Experian Company, that is composed of 577 organizations with at least one balance sheet or trial balance. The data were analyzed by using Microsoft Office Access, and for that, it has been identified 19 financial indicators, drawn from the balance sheets of entities, which enabled the classification of the entities. With that indicators, it was evaluated the sustainability and the key features, considering the region where they operate and the activity they practice. Not all the entities had all the information defined in the indicators, so not all the entities have been evaluated. In the analysis of management indicators became evident that not all entities disseminate information on issues related to management and transparency. The existence of information can improve the performance of the entity, depending on its quality. The main feature observed in the structures is the low concern for the dissemination of information, which reduces transparency and makes it difficult to search for resources to ensure sustainability. In this sense, the main challenge of Social Assistance is to improve and professionalize the management